The Australian health system response to COVID-19 from a resilient health care perspective: what have we learned? - Robyn Clay-Williams; Jeffrey Braithwaite (Sax Institute, 2020)
As of late 2020, Australia's response to the coronavirus disease 2019 (COVID-19) pandemic has been relatively successful in comparison with responses in Northern Europe and the US - but what have we learned? In this perspective, we used a resilient health care approach to frame the health system response in three key Australian states (New South Wales, Victoria and Queensland) with large and diverse population groups. We assessed their response in terms of four resilience capacities: how did Australian health authorities monitor public health to enable anomalies to be detected; how did they anticipate the emerging COVID-19 crisis; how did they respond to the pandemic; and what did they learn from this experience? Increased system agility and new ways of working, including contact tracing, telehealth and resource-sharing, are now available to underpin Australia's response to future challenges or other unexpected events.